Endoscopic Dilation with Bougies versus Balloon Dilation in Esophageal Benign Strictures: Systematic Review and Meta-Analysis - Iatagan R. Josino; Antônio C. Madruga-Neto; Igor B. Ribeiro; Hugo G. Guedes; Vitor O. Brunaldi; Diogo T. H. de Moura; Wanderley M. Bernardo; Eduardo G. H. de Moura (Gastroenterology Research and Practice)
Background. The use of bougies and balloons to dilate benign esophageal strictures (BES) is a consolidated procedure. However, the amount of evidence available in scientific literature supporting which is the best technique is very low, despite the great prevalence and importance of such pathology. This systematic review with meta-analysis aims at comparing both techniques, providing good quality of evidence. Methods. We searched for randomized clinical trials (RCTs) published from insertion to November 2017, using MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, LILACS, and grey literature. After the data extraction, a meta-analysis was performed. The main outcomes were symptomatic relief and recurrence rate. The secondary outcomes were bleeding, perforation, and postprocedure pain. Results. We included 5 randomized clinical trials (RCTs), totalizing 461 patients. Among them, 151 were treated with bougie dilation and 225 underwent balloon dilation. Regarding symptomatic relief, recurrence, bleeding, and perforation rates, there were no differences between the methods. Concerning postprocedure pain, patients submitted to balloon dilation had less intense pain (RD 0.27, 95% IC −0.42 to −0.07, P=0.007). Conclusion. We conclude that there is no difference between bougie and balloon dilation of BESs regarding symptomatic relief, recurrence rate at 12 months, bleeding, and perforation. Patients undergoing balloon dilation present less severe postprocedure pain.